2011
DOI: 10.1111/j.2040-1124.2011.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of glucose tolerance on the severity of non-alcoholic steatohepatitis

Abstract: Aims/Introduction:  We investigated the relationship between non‐alcoholic steatohepatitis (NASH) and different stages of fasting plasma glucose (FPG) concentrations, and the association between factors related to glucose tolerance and severity of NASH.Materials and Methods:  A total of 147 patients with non‐alcoholic fatty liver disease (NAFLD) who had undergone a liver biopsy were divided into three groups: a normal glucose tolerance (NGT) group, an impaired fasting glucose (IFG) group and a diabetes (DM) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…The overall study, summarized in a schematic diagram ( Figure 6), demonstrate potential markers and their significance in early detection and prognosis of NAFLD and associated pathology. Dyslipidemia is characterized by altered level of lipids, lipoproteins and impaired glucose tolerance, evidenced by the increased level of FBG, predisposes patients to various metabolic disorders including NAFLD [61,62]. Our results are in concordance, as the system lipid profile was severely altered in our obese and diabetic patients with or without fatty infiltration of liver.…”
Section: Discussionsupporting
confidence: 86%
“…The overall study, summarized in a schematic diagram ( Figure 6), demonstrate potential markers and their significance in early detection and prognosis of NAFLD and associated pathology. Dyslipidemia is characterized by altered level of lipids, lipoproteins and impaired glucose tolerance, evidenced by the increased level of FBG, predisposes patients to various metabolic disorders including NAFLD [61,62]. Our results are in concordance, as the system lipid profile was severely altered in our obese and diabetic patients with or without fatty infiltration of liver.…”
Section: Discussionsupporting
confidence: 86%
“…We previously investigated the association between factors related to glucose tolerance and the severity of NASH in Japanese patients with NAFLD. Although we found no correlations between the fasting plasma glucose and either the total NAFLD activity score or the stage of NASH, the fasting serum insulin level was significantly correlated with both, even after adjustments for age, sex and body mass index (BMI).…”
Section: Introductionmentioning
confidence: 65%
“…Hyperinsulinemia and increased insulin resistance could have important roles in the pathogenesis of NASH in both Western and Asian countries, and improvement of the insulin sensitivity has been reported to reverse some of the clinical manifestations and histological changes in NASH. We have also shown the possible important role of hyperinsulinemia in the pathogenesis of NASH in humans. Furthermore, we recently showed that long‐term high‐fat (HF) diet loading was sufficient to induce NASH in C57bl/6J mice, and that the amelioration of obesity and hyperinsulinemia, by switching from the HF diet to a standard chow diet, protected against the development of NASH in the same mice without any changes of the blood glucose levels.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that factors other than adiposity may contribute to insulin resistance in NAFLD, which is compatible with our present finding that the severity of histological findings affects insulin sensitivity in NAFLD independently of BMI in multiple regression analysis. In previous reports, histological severity in NAFLD was significantly correlated with insulin sensitivity/resistance indices, but these results were not necessarily adjusted with BMI [ 33 35 ]. Our present results also accord with a recent report that severity of histological findings correlates with insulin sensitivity after adjustment for BMI [ 36 ].…”
Section: Discussionmentioning
confidence: 95%